Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) Berbantuan Media Gambar Terhadap Hasil Belajar Ilmu Pengetahuan Alam Siswa Kelas IV SDN 4 Cakranegara Tahun Pelajaran 2019/2020 - Mirajul Mukmin; Muhammad Liwa Ilhamdi; Husniati Husniati (Indonesian Publication Center, 2020)
ABSTRACT This study aims to determine the effect of the Numbered Heads Together (NHT) learning model assisted by picture media on the learning achievement of science students in grade IV SDN 4 Cakranegara in the academic year 2019/2020. This type of research is a quasi experiment with a nonequivalent control group design. The population in this study were all fourth grade students of SDN 4 Cakranegara in the academic year 2019/2020. the technique of selecting samples in this study is non-probability sampling using saturated samples. Samples in this study were students in class IVa (experimental class) with 18 students and IVb (control class) with 18 students in SDN 4 Cakranegara. The instrument used to obtain learning achievement is a multiple choice question, the hypothesis test that used is the independent sample t test assist by SPSS 22.0 for windows at a significance level of 5%. The data obtained shows that the experimental class student learning achievement are 68.05 for pree-test and 74.44 for post-test while the control class student learning achievement are 58.88 for pree-test and 72.77 for post-test. From the results of the t arithmetic = 2.540 and t table = 2.032, which means t arithmetic (2,540)> t table (2,032), the results of statistical analysis means that the learning achievement of experimental class students are significantly better than the control class. So it can be concluded that, there is an influence of the Numbered Heads Together (NHT) model with the assistance of Image Media on the Science Learning achievement of Grade IV Students of SDN 4 Cakranegara Academic Year 2019/2020